Ani’s portals of the second quarter of the 11th century: Interpretations of ideas - Kazaryan, Armen (project baikal, 2024)
The second part of the study presents an analytical review covering more than twenty portals of the second quarter of the 11th century – the reign of the last Shahinshahs of the Armenian kingdom and the heyday of monastic construction throughout the country. The article reveals the specificity of the samples of two main types of portals conventionally called arched and Hellenistic. Attention is drawn to the most striking works, especially the portal of the church in the fortress of Amberd, which composition incorporated the features of these two types.